أثر التسميد الأخضر بنبات الترمس الأبيضLupinus albus L. في نمو وإنتاجية محصول البطاطا Solanum tuberosum L - زيدان, رياض; خليل, نديم; عثمان, جنان (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في عروة ربيعية خلال الموسمين الزراعيين 2007/2008 و2008/2009 في مشتل جامعة تشرين، بهدف دراسة أثر التسميد الأخضر بنبات الترمس الأبيض في نمو وإنتاجية محصول البطاطا (الصنف دراجا)، كبديل للأسمدة العضوية ذات المصدر الحيواني. أظهرت النتائج الأثر الإيجابي للتسميد الأخضر في زيادة كل من مساحة المسطح الورقي للنبات ودليله وعدد السوق الهوائية وارتفاعها، وعدد درنات النبات، ومتوسط وزن الدرنة، فضلاً عن دوره في تحسين الإنتاج التسويقي ورفع إنتاجية النبات من الدرنات الكبيرة . The present work was carried out for two successive years in the spring seasons 2007/2008 and 2008/2009, at the Agriculture Faculty, to investigate the growth and production of potato variety Draga under green manure conditions with Lupinus albus.L, as an alternative source of organic manure. The results showed a positive effect of green manure on the surface foliage, foliage index, stem length and number per plant, weight average of tubers, number of plant tubers, and the increase of large tubers' production.